108k views
3 votes
Please answer quickly.

1. Solve by the linear combination method.

3x – 5y = 7
2x + 3y = 30



(3, –7)


(9, 4)


(3, 7)


(–3, –7)

2. Solve by the linear combination method.

2x + 3y = –17
5x + 2y = –4




(3, –1)


(–2, 2)


(–1, 3)


(2, –7)

3. Solve by the linear combination method.

x + y = 50
0.05x + 0.06y = 2.8




(20, –50)


(10, 30)


(20, 30)


(40, 60)

4. Solve by the linear combination method.

8g – 5h = 7
4g + 10h = 1

(-3/4, -1/5)

(-3/4, 1/5)

(3/4, -1/5)

(3/4, 1/5)

User Yanni Wang
by
5.7k points

1 Answer

2 votes

Answer:

1. B. (9, 4)

2. D. (2, -7)

3. C. (20, 30)

4. C. (3/4, -1/5)

Explanation:

1.

Eq.1 3x – 5y = 7 Multiply by -2.

Eq. 2 2x + 3y = 30 Multiply by 3.

Eq. 1 becomes: -6x + 10y = -14

Eq. 2 becomes: 6x + 9y = 90

Add the two new equations to get:

19y = 76

y = 4

Now substitute 4 for y in the first original equation and solve for x.

3x - 5(4) = 7

3x -20 = 7

3x = 27

x = 9

Answer: (9, 4)

2.

2x + 3y = -17 Multiply by -2

5x + 2y = -4 Multiply by 3

-4x - 6y = 34

15x + 6y = -12

Add last two equations.

11x = 22

x = 2

Substitute x = 2 into first original equation and solve for y.

2x + 3y = -17

2(2) + 3y = -17

4 + 3y = -17

3y = -21

y = -7

Answer: D. (2, -7)

3.

x + y = 50 Keep equation as it is.

0.05x + 0.06y = 2.8 Multiply by -20.

x + y = 50

-x - 1.2y = -56

Add last two equations.

-0.2y = -6

y = 30

Substitute y = 30 in first original equation and solve for x.

x + y = 50

x + 30 = 50

x = 20

Answer: C. (20, 30)

4.

8g - 5h = 7 Keep as is.

4g + 10h = 1 Multiply by -2.

8g - 5h = 7

-8g - 20h = -2

Add last two equations.

-25h = 5

h = -1/5

Substitute h = -1/5 into h of first original equation and solve for g.

8g - 5h = 7

8g - 5(-1/5) = 7

8g + 1 = 7

8g = 6

g = 6/8

g = 3/4

Answer: C. (3/4, -1/5)

User Aolde
by
5.8k points